F-111D, DT and E Evaluation of Environmental Control, Airframe, Flight Control, and Secondary Power Subsystems. Appendix 1 - Olson, Richard W (1973)
During the arctic test phase of the F-111D DT/E All-Weather Test Program, 24.0 hours of test time were accumulated in 12 test flights. Five of these flights were selected as being most representative of aircraft operation in an arctic environment. All available data obtained on these five flights are presented in this document as computer printouts. Appendix 1 to ADB002372. See also Appendix 2, ADB002374.